Analisis Puasa Romadon Dengan Puasa Sunnah (Nasikh wa al-Mansukh) - Dame Siregar (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2020)
The Prophet Dawud's fast is the first obligatory fast to be practiced by the Prophet in the month of Romadon, 1 SH. Number of days 354: 2 + 177 days. This fasting was practiced by the Prophet since the month of Romadon knew 1 SH after Prophet Isro 'and mi'roj in 1 AH until the month of Robiul at the beginning of 1 H. The fast of David had not explained the double reward. This fast is a baid fast or 3-day fast carried out on the 13,14 and 15 of each month, starting in 1 H. 3X10 = 30 days, the amount of 1 year 3X12 = 36 days X 10 reward = 360. Dawud fast = 177 days. Then in the month of Sha'ban in the 2nd year of H, the order of the Romadon fasting began in the month of Sha'bannya, to translate the Pausa Baid. In the month of Shawwal in the second year of H, a hadith about the sunnah fasting for 6 days of the month of Shawwal was issued, also a hadith on fasting Monday came out. Two observations of this hadith must be compromised. Namely the 6 days of the month of Shawwal are fasting Monday and Thursday. The minimum number of 6 days can be practiced in the month of dzuilhijjah. Because if 'Idil Adha' is Monday then Thursday, then the total is 4X2 = 8 days-2 days = 6 days, otherwise it can be 8 days. Then came out a hadith about fasting on jumu'ah, with the condition that the previous fast was Thursday, if there is an obstacle then the fast afterward is Saturday. Fasting mandatory romadon = 30 days + with fasting sunnah on Monday, Thursday and jumu'ah. 12X11 = 132 = 362 days. Dawud fasting 177 days - 362 = 15 days. Illegal fasting 5 days a year remaining = 10 days. The rest is the time for the qodo fast, nazdar kaffaroh on the other Mondays, Thursdays and jumu'ah. Besides this 3rd day. Finally, the current fasts with the Prophet Dawud's fast are almost the same at once. And this is the meaning of the verse كَمَا which means the same as QS al-Bqoroh 2: 183. The mandatory romadon fast and the sunnah fast is quite enough on Mondays and jumu'ah.